Game Design as Emancipatory Praxis: A Case Study in Popular Education - Kamil M. Gerónimo-López (Adult Education Research Conference, 2025)
This study examines how participatory game design fosters systemic literacy, conscientization, and social transformation within Popular Education. Using a case study of Pueblo Crítico, it explores design as an emancipatory praxis through Participatory Design-Based Research.
Keywords: Popular Education; game design; Participatory Design-Based Research; emancipatory education; conscientization